These happy golden years - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : HarperTrophy, 1971)
Fifteen-year-old Laura learns that living away from home and teaching school can be a bit frightening when most of the students are taller than she is, but every week Almonzo Wilder arrives to take her to her family for the weekend.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Teachers -- Fiction; Courtship -- Fiction; Frontier and pioneer life -- South Dakota -- Fiction; Family life -- South Dakota -- Fiction; South Dakota -- Fiction